The Philosopher’s Autobiography: A Qualitative Study - Joseph Kaipayil (Journal of Dharma, 2004)
Shlomit C. Schuster is a well-known practitioner of philosophical counselling, based in Jerusalem. Her earlier book, Philosophy Practice: An Alternative to Counseling and Psychotherapy (Westport, CT: Praeger Publishers, 1999), contributed significantly to the solidification of the emergent field of philosophical counselling (also called philosophical practice). The present book is still another contribution to the field, but with a difference.